Analisis Kuantitas dan Kualitas Air Sumur Bor dan Air Sumur Gali Untuk Pemenuhan Sumberdaya Air Di Desa Battu Winangun Kecamatan Lubuk Raja Kabupaten Ogan Komering Ulu - Eka Rizki Meiwinda; Lucyana; Azwar; Ali Mas'ud Dwi Cahyo (Rumah Jurnal PT Citra Air Nusantara, 2025)
Water quantity refers to the amount of clean water needed to meet daily needs. Water quality generally indicates the quality or condition of water associated with a particular activity or need. The limited capabilities and knowledge of the surrounding community necessitate testing the quality and quantity of drilled and dug well water in Battu Winangun Village to provide information to the community regarding good water quality and information on whether or not the water source can be used for drinking water and for daily activities from a physical and chemical perspective. The research method used was observation and interviews to obtain primary and secondary data. The results obtained were that the availability of drilled and dug well water in each hamlet exceeded and was sufficient to meet daily water needs. The quality of drilled and dug well water according to the test results showed that drilled and dug well water, based on physical parameters, met standard requirements.